Utilizing Generative AI To Increase The Creativity of Msme Educators And Course Institutions For Operational Cost Efficiency in Education Businesses: Pengabdian - Kusiyah; Retno Dewi Wijiastuti; Liestyowati; Sulaeman; Fitriani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector in education and Course and Training Institutions (LKP) in Indonesia face significant challenges in the form of high operational costs for producing teaching materials, promotional materials, and administrative burdens. On the other hand, the adoption of intelligent technologies such as Generative Artificial Intelligence (GenAI) is still very limited due to the disparity in digital literacy between regions. This Community Service (PkM) activity aims to increase the creativity of educators and course institution managers in utilizing GenAI technology (such as ChatGPT, Claude, Midjourney, and Canva AI) to optimize the efficiency of operational costs for educational businesses. This program is implemented collaboratively across regions in eight LKP and MSME education partners spread across four large islands in Indonesia, namely: LKP Wahana Edukasi Medan City and LKP Cerdas Mandiri Palembang City ( Sumatra ); LKP Bina Karya Bandung City and LKP Bahasa Nusantara Sleman Regency ( Java ); LKP Borneo Digital Samarinda City and LKP Khatulistiwa Mandiri Pontianak City ( Kalimantan ); as well as LKP Mamminasata Makassar City and LKP Sulut Vokasi Manado City ( Sulawesi ). The implementation method of the activity was designed through a Training of Trainers (ToT) approach, interactive project -based learning workshops, and intensive mentoring for three months. The results of the community service showed an increase in educators' capabilities in developing AI-based teaching modules by 84%, efficiency of time for creating learning materials by up to 65%, and a decrease in production costs for marketing content and operational teaching materials by 42%. This GenAI-based digital transformation has proven effective in driving financial efficiency and the sustainable competitiveness of educational MSME businesses in the region.